Some properties of the ideal of continuous functions with pseudocompact support - E. A. Abu Osba; H. Al-Ezeh (International Journal of Mathematics and Mathematical Sciences)
Let C(X) be the ring of all continuous real-valued functions defined on a completely regular T1-space. Let CΨ(X) and CK(X) be the ideal of functions with pseudocompact support and compact support, respectively. Further equivalent conditions are given to characterize when an ideal of C(X) is a P-ideal, a concept which was originally defined and characterized by Rudd (1975). We used this new characterization to characterize when CΨ(X) is a P-ideal, in particular we proved that CK(X) is a P-ideal if and only if CK(X)={f∈C(X):f=0 except on a finite set}. We also used this characterization to prove that for any ideal I contained in CΨ(X), I is an injective C(X)-module if and only if coz I is finite. Finally, we showed that CΨ(X) cannot be a proper prime ideal while CK(X) is prime if and only if X is an almost compact noncompact space and ∞ is an F-point. We give concrete examples exemplifying the concepts studied.